Partnership or insanity: why do health partnerships do the same thing over and over again and expect a different result?. Issue 1 (January 2020) - Perkins, Neil; Hunter, David J; Visram, Shelina; Finn, Rachael; Gosling, Jennifer; Adams, Lee; Forrest, Amanda
Objectives: The paper reports on an empirical study of Health and Wellbeing Boards (HWBs) in England. Established by the Health and Social Care Act 2012, HWBs act as place-based hubs for leaders in health, social care, local government and other sectors to come together to address health improvement and the wider determinants of health. Methods: We conducted a three-year study of HWBs (2015–2017) in five localities across England. This involved collecting qualitative data from semi-structured interviews with key actors in the HWBs at strategic and operational levels, and focus group sessions with voluntary-sector participants at each HWB. Results: HWBs have largely followed the path of previous partnerships in terms of a lack of clear aims and objectives, lack of ownership and accountability by partners, and an absence of any significant impact on health outcomes. Conclusions: Many of the features of unsuccessful partnership working were largely displayed by HWBs. Boards require more executive power and ownership from the bottom up if they are to have any real impact.